2021
DOI: 10.1021/acs.energyfuels.1c00090
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Brine Effect on Asphaltene Precipitation and Deposition during Water Injection in Porous Media Using Static and Dynamic Systems

Abstract: Asphaltene precipitation and deposition in porous media damages formation by reducing permeability and altering wettability, resulting in a significant reduction in reservoir oil production. Although the effects of some factors such as temperature, pressure, and composition have been studied over time, the effects of others, such as emulsified brine, remain uncertain and the available data in this area is limited. Most importantly, the effect of brine injection on deposition has never been studied in previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…Doryani et al indicated that divalent cations intensify the asphaltene precipitation more than monovalent cations. An identical result is reported by Shahsavani et al However, Alizadeh and Soltani Soulgani concluded that asphaltene precipitation does not necessarily intensify in the presence of divalent cations since Ca 2+ and Na + showed a similar effect on asphaltene instability.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Doryani et al indicated that divalent cations intensify the asphaltene precipitation more than monovalent cations. An identical result is reported by Shahsavani et al However, Alizadeh and Soltani Soulgani concluded that asphaltene precipitation does not necessarily intensify in the presence of divalent cations since Ca 2+ and Na + showed a similar effect on asphaltene instability.…”
Section: Introductionsupporting
confidence: 83%
“…However, with a further increase in salinity to 45,000 ppm, asphaltene precipitation reduced. In 2021, Alizadeh and Soltani Soulgani observed that the asphaltene precipitation increases with an increase in water content, as has been reported by Asaadian et al . Furthermore, their studies on salt concentration revealed that the amount of asphaltene precipitation increases with an increase in salinity to the range of 25,000 to 40,000 ppm and then decreases.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The interactions between fluids as a function of fluids composition, strongly affect the recovery factor of low salinity water flooding. Alizadeh and Soulgani investigated the effect of low salinity water injection on asphaltene precipitation in an oil (23.51 °API) at 25 °C. The asphaltene content was 6.5 wt %.…”
Section: Emulsion In Injected Water/brinementioning
confidence: 99%